2008
DOI: 10.1021/jm800524s
|View full text |Cite
|
Sign up to set email alerts
|

Hit Identification and Binding Mode Predictions by Rigorous Free Energy Simulations

Abstract: The identification of lead molecules using computational modeling often relies on approximate, highthroughput approaches, of limited accuracy. We show here that, with a methodology we recently developed, it is possible to predict the relative binding free energies of structurally diverse ligands of the estrogen receptor-R using a rigorous statistical thermodynamics approach. Predictions obtained from the simulations with an explicit solvation model are in good qualitative agreement with experimental data, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 73 publications
2
69
0
Order By: Relevance
“…Michel et al used dual-topologies to compute the relative free energy between different potential binding modes of the same ligands, 107,108 highlighting the fact that adequate sampling over binding modes is not guaranteed, nor is the binding mode always obvious. Here, subtle differences in ligand composition could easily alter the binding mode, 107 and stable binding modes differed by 1 kcal/mol 107 to 7 kcal/mol.…”
Section: E Binding Modes Are Difficult To Predictmentioning
confidence: 99%
See 1 more Smart Citation
“…Michel et al used dual-topologies to compute the relative free energy between different potential binding modes of the same ligands, 107,108 highlighting the fact that adequate sampling over binding modes is not guaranteed, nor is the binding mode always obvious. Here, subtle differences in ligand composition could easily alter the binding mode, 107 and stable binding modes differed by 1 kcal/mol 107 to 7 kcal/mol.…”
Section: E Binding Modes Are Difficult To Predictmentioning
confidence: 99%
“…Here, subtle differences in ligand composition could easily alter the binding mode, 107 and stable binding modes differed by 1 kcal/mol 107 to 7 kcal/mol. 108 One other study of particular interest highlighted multiple binding modes of catechol-O-methyltransferase inhibitors which had to be treated separately in relative calculations because of time scale issues.…”
Section: E Binding Modes Are Difficult To Predictmentioning
confidence: 99%
“…1,5,8,[16][17][18][19][20] However, it has not been demonstrated that highly accurate results can be achieved reliably across a wide range of ligands and protein targets, as would be needed for the method to be useful in industrial pharmaceutical research programs.…”
Section: Introductionmentioning
confidence: 99%
“…In the dual topologies approach, the computational morphing process carries along two ligand molecules at the same time throughout all simulations. [14][15][16] Using this method, the simulations begin with both a "real" ligand A and a "dummy" ligand B, and over the course of the alchemical transformation, A becomes the dummy ligand while B becomes the real ligand. That is, in the initial state the non-bonded interactions of B are fully decoupled from the rest of the system (the protein and the solvent) and in the final state the nonbonded interactions of A are fully decoupled.…”
Section: Introductionmentioning
confidence: 99%
“…16 Other methods use constraints--non-energetic terms which are enforced at each timestep-to connect A and B, in some instances by performing identical MC moves on both ligands. 14,15 Restraints which connect A to B do not alter the rotational and translational entropy of either ligand in the fully coupled state, because even though the fully coupled A is always attached to B, B does not interact with the environment and thus does not alter the free energy landscape felt by A.…”
Section: Introductionmentioning
confidence: 99%